Analisis Penyebab Kecenderungan Perilaku Menimbun Barang pada Mahasiswa - Alfian Ahmad Zahir; Arundati Shinta; Izzah Annisatur Rahma (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2025)
Hoarding behavior refers to the excessive accumulation of items, which can interfere with the functionality of living spaces and the individual’s psychological well-being. Although many studies have examined hoarding, research specifically focusing on this behavior among university students remains limited. This study aims to analyze the causes of hoarding tendencies among students by considering psychological, social, and environmental factors. The method used is a qualitative approach with in-depth interviews conducted on two subjects one male and one female student who exhibit hoarding tendencies. The findings reveal that both subjects display hoarding tendencies influenced by various aspects, such as emotional attachment to objects, difficulty making decisions to discard items, family environmental influences, and neurobiological factors such as anxiety and poor emotional control. In addition, sentimental value and the belief that items may be useful in the future further reinforce the habit of keeping possessions. The conclusion of this research emphasizes that hoarding behavior among students results from a complex interaction between psychological aspects (emotions, beliefs, anxiety), social aspects (family influence), and environmental aspects (living alone, academic pressure). Therefore, an integrated intervention approach is needed, both emotionally and practically, such as raising awareness, relaxation techniques, and the structured application of decluttering strategies, to prevent the development of more severe hoarding disorders.